Seventeen-level cascaded switched-capacitor multilevel inverter for grid-connected photovoltaic systems - Naser, Maytham Jasim; Hassan, Turki Kahawish (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
This paper proposes a single-phase photovoltaic (PV) multi-array single DC bus seventeen-level cascaded switched capacitor multi-level inverter (CSC-MLI). Two boost converters are employed to extract maximum power, one for each PV string, and the output of each boost converter is connected to a single DC bus collector. A new 17-level CSC-MLI topology has been proposed to produce seventeen output voltage levels with a boosting ability of 2 times and the capability of limiting the capacitors' inrush current during the capacitors' charging mode. The topology offers a lower total standing voltage (TSV) of 16.5 as well as utilizes a lower number of components compared to conventional inverters. A total harmonic distortion (THD) of only 8.12% is present in the output voltage waveform, which yields a high-quality injected grid current through a simple filter with a THD of 1.18%. This design utilizes the switched-capacitor technique and has a self-voltage balancing feature. A novel hybrid-PWM technique has been implemented on CSC-MLI with a switching frequency of 2.5 kHz. The topology of the 3 kW single-phase 17-level inverter demonstrated commendable steady-state and dynamic performance across a range of test conditions by using MATLAB/Simulink software.